Sensitive surface plasmon resonance performance of cadmium sulfide quantum dots-amine functionalized graphene oxide based thin film towards dengue virus E-protein - Sheh Omar, Nur Alia; Yap, Wing Fen; Abdullah, Jaafar; Mat Zaid, Mohd Hazani; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Mahdi, Mohd Adzir (Elsevier, 2019)
An optical sensor for the dengue virus (DENV) E-protein based on cadmium sulfide quantum dots composited with amine functionalized graphene oxide (CdS-NH2GO) thin film was successfully developed. A specific monoclonal antibodies (IgM) were covalently attached to CdS-NH2GO via EDC/NHS coupling to sense targeted E-proteins. The SPR sensor exhibited an excellent detection limit (0.001 nM/1 pM) with sensitivity of 5.49° nM−1 for the detection of DENV E-protein. The binding affinity, as well as the performance of the Au/CdS-NH2GO/EDC-NHS/IgM film, was successfully obtained at 486.54 nM−1 in detecting DENV E-proteins. These results indicated that the Au/CdS-NH2GO/EDC-NHS/IgM film shows high potential sensitive and stronger binding towards DENV E-protein.